2016
DOI: 10.1021/acs.jchemed.6b00254
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Educational Benefits in Half the Time: An Alternating Organic Chemistry Laboratory Sequence Targeting Prehealth Students

Abstract: The laboratory is a mainstay in STEM education, promoting the development of critical thinking skills, dexterity, and scientific curiosity. The goals in the laboratory for nonchemistry, prehealth majors, though, could be distinguished from those for chemistry majors. In service courses such as organic chemistry, much laboratory time is often spent building discipline-specific technical skills that poorly align with the postgraduate goals of prehealth students. To address the needs of students in Muhlenberg Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Our meaningful learning approach requires continually building off skills gained earlier in the course, and as a consequence, fewer techniques can be introduced within the semester. Consistent with the less-is-more philosophy, Young et al have shown that students who performed half as many experiments as the traditional course performed similar to, and in some cases better than, students enrolled in the traditional lab course . Another limitation is that the meaningful learning approach can be diminished when the instructors provide answers to maximize time efficiency and minimize student struggles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our meaningful learning approach requires continually building off skills gained earlier in the course, and as a consequence, fewer techniques can be introduced within the semester. Consistent with the less-is-more philosophy, Young et al have shown that students who performed half as many experiments as the traditional course performed similar to, and in some cases better than, students enrolled in the traditional lab course . Another limitation is that the meaningful learning approach can be diminished when the instructors provide answers to maximize time efficiency and minimize student struggles.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the less-is-more philosophy, Young et al have shown that students who performed half as many experiments as the traditional course performed similar to, and in some cases better than, students enrolled in the traditional lab course. 36 Another limitation is that the meaningful learning approach can be diminished when the instructors provide answers to maximize time efficiency and minimize student struggles. To attenuate this concern, we provide training on the meaningful learning approach to the graduate student instructors at the start of the term.…”
Section: Limitationsmentioning
confidence: 99%
“…This would allow deeper focus on foundational Organic Chemistry topics to prepare students for biochemistry, enzyme kinetics, and pharmacology. 18 In addition to nomenclature and chemical structures, instructors could focus on using real-world examples of medications and their chemical reactions. 14 This would allow a potent lesson in both Pharmacology and Organic Chemistry, especially if it were used in the setting of a clinical vignette that would highlight the value in understanding such detail.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Although there is overlap between the experiments performed in each organic chemistry course, there is a key difference in lab schedules. While the students in the majors course attend lab every week, the students in the large, nonmajors course participate in an alternating laboratory sequence in which hands-on laboratory experiences are alternated with activities performed outside of the lab . Students enrolled in this model spend about half the time in lab compared to a typical laboratory experience, although they do build lab-related skills (e.g., data analysis) during their off weeks.…”
Section: Participants and Institutional Settingmentioning
confidence: 99%
“…As mentioned previously, these interlab collaborations were initially designed to complement our alternating laboratory sequence for prehealth students . Although assessment data suggest that the learning goals of the laboratory for this group of students are still achieved, one clear limitation of the alternating model is that it precludes the performance of multiweek experiments that are so integral to the organic chemistry laboratory. , Even with traditional (i.e., weekly) laboratories, a 6+ week experiment is difficult to accommodate, unless the entire semester is dedicated to the same project. , These interlab collaborations complement our alternating laboratory sequence by providing the flexibility to implement longer, project-focused laboratories that approach research experiences without spending the entire semester on one experiment.…”
Section: Overview Of Collaborative Laboratory Modelmentioning
confidence: 99%